2009
DOI: 10.1002/ijc.24116
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and type distribution of human papillomavirus in carcinoma and intraepithelial neoplasia of the vulva, vagina and anus: A meta‐analysis

Abstract: This meta-analysis investigated human papillomavirus (HPV) prevalence in vulvar, vaginal and anal intraepithelial neoplasia (VIN, VAIN, AIN) grades 1-3 and carcinoma from 93 studies conducted in 4 continents and using PCR assays. Overall HPV prevalence was 67.8%, 85.3% and 40.4% among 90 VIN1, 1,061 VIN2/3 and 1,873 vulvar carcinomas; 100%, 90.1% and 69.9% among 107 VAIN1, 191 VAIN2/3 and 136 vaginal carcinomas; and 91.5%, 93.9% and 84.3% among 671 AIN1, 609 AIN2/3 and 955 anal carcinomas, respectively. HPV16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

57
628
14
39

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 836 publications
(738 citation statements)
references
References 36 publications
57
628
14
39
Order By: Relevance
“…The most common HPV types in VAIN2/3 were HPV16 (57.6%), 18 (6.9%) and 58 (5.9%). 9 Our results indicate that the leading HPV types were HPV16 (35.5%), HPV58 (9.9%), HPV52 (9.9%), HPV39 (8.4%), HPV33 (7.3%) and HPV53 (7.0%). Notably, HPV18 was rare (2.7%) in VAIN samples in our study.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…The most common HPV types in VAIN2/3 were HPV16 (57.6%), 18 (6.9%) and 58 (5.9%). 9 Our results indicate that the leading HPV types were HPV16 (35.5%), HPV58 (9.9%), HPV52 (9.9%), HPV39 (8.4%), HPV33 (7.3%) and HPV53 (7.0%). Notably, HPV18 was rare (2.7%) in VAIN samples in our study.…”
Section: Discussionmentioning
confidence: 57%
“…3,4 The review by Smith et al 8 found HPV positivity in 98.5% of VAIN1 samples and in 92.6% of VAIN2/3 samples. De Vuyst et al 9 reported HPV positivity in 100% of VAIN1 samples and in 90.1% of VAIN2/3 samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations